Evolution of software from the perspective of systems - О. Ліневич; О. Лісовиченко (Adaptivni Sistemi Avtomatičnogo Upravlinnâ, 2024)
The objects of research are development methods that accelerate the evolution of software. The article provides an overview of widely used development methods and a new universal method, identifies the reasons for the long and unpredictable evolution of systems, as well as the advantages of the new method for accelerating evolution. A total of 8 methods were analyzed, which include abstraction method, DDD, TDD, BDD, API Design First, RUP, hybrid and new universal methods. The purpose of the work is to speed up the software evolution process. To achieve the goal, a new method is proposed that analyzes the data and processes of use cases as separate systems and consistently combines them with the help of general systems theory.